SYSTEMATIC LITERATURE REVIEW ON NEUROSCIENCE OF CONCEPTUAL LEARNING IN MATHEMATICS - Wan Norliza Wan Bakar; Noor Suzana Shahidan (Jurnal Penyelidikan Sains Sosial, 2021)
Conceptual learning in Mathematics is defined as the tactical reasons why operationregarding numerical value works as they do. Neuroscience in Mathematics explained aboutbrain activation that occurs while studying the subject. A systematic literature studies havebeen done to analyze past studies related to pin point the Neuroscience of Conceptual Learningin Mathematics. Literature studies from Google Scholar, ERIC, ScienceDirect and Springerhave been used to get informations on these relationship. The overall findings shown that it isreassuring to observe that the current emphasis of the significance of inhibitory managementtechnology and arithmetic, which emerges from the cognitive neuroscience studies, is totallyconsistent with older practice to inspire students to take a ‘ready time’ earlier than respondingthroughout technology lessons. While there is already vast experience amongst instructors thatinhibitory management is a foundational ability in arithmetic and cognitive neuroscience hasproof to improve this conviction and similarly enhance practice.